Do maturation, anthropometrics and leg muscle qualities influence repeated change of direction performance in adolescent boys and girls? - Giuriato, Matteo; Carnevale Pellino, Vittoria; Lovecchio, Nicola; Codella, Roberto; Vandoni, Matteo; Talpey, Scott (Biology of Sport, 2023)
The ability to change direction rapidly is a key fitness quality especially in invasive sports where young players perform approximately 300 changes of direction in a game. There iscurrently limited understanding of how anthropometric characteristics and maturation status influence change of direction ability in adolescent. Therefore, the purpose of this investigation is to assess the influence of anthropometrics and maturation status on change of direction ability in young people. The study involved 706 adolescents (367 girls) aged 14 19-yearold attending the same high school in Northern Italy. Stature, body mass, seated height and leg length were measured to determine the anthropometrics and maturation status of the participants. Repeated change of direction ability (10×5 m shuttle run test), lower limb power and muscle strength were evaluated using field tests from the Eurofit test battery. Maturity offset was calculated separately for boys and girls, in accord with the equation proposed by Mirwald. Preliminary analysis with 10×5 m as a dependent variable and sex and PHV as a fixed factor, suggests a significant difference between sex (p < 0.001; d = 0.35) but not with PHV (p = 0.986; d = 0.000) and interaction PHV×sex (p = 0.836; d = 0.000). Our results suggested that repeated change of direction performance wasinfluenced by anthropometrics, maturation and muscle qualitiesin adolescent boys and girls.